TI_GERICHTE 52.2010.341 vom 10. Februar 2011 , Rilascio di un permesso di dimora CE/AELS per lavorare come indipendente - TI Tribunale d'appello (2011)
Rilascio di un permesso di dimora CE/AELS per lavorare come indipendente